ON A NEW SPECIES RHABDOCHONA MARINA (NEMATODA : RHABDOCHONIDAE) FROM THE INTESTINE OF PEMPHERIS VANICOLENSIS (CUVIER) OF VISAKHAPATNAM - BHARATHALAKSHMI, B.; SUDHA, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1999)
The present paper deals with description of a new nematode species of the family Rhabdochonidae Skrjabin, 1946 from the intestine of marine fish Pempheris vanicolesis (Cuvier) of Visakhapatnam. The specimens do not agree with descriptios of known species of the genus Rhabdochona, hence a new species Rhabdochona marina has been erected to accommodate the present specimens. The new species could be distinguished by body measurements, location of nerve ring and cervical papillae, number of longitudinal ridges supporting buccal capsule, length of muscular and glandular oesophagus, number and arrangement of caudal papillae, size of spicules and position of vulva.